Proses Pendidikan dalam Korelasi Pemikiran Paulo Freire dan Spiritualitas Fransiskus Asisi - Malau, Desna Suryanita; Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2023)
Paulo Freire's philosophical thinking and the spirituality of Francis of Assisi can inspire the world of education in Indonesia. The reality of educational process in schools in Indonesia still needs further reflection on whether it is truly liberating and transforming those who are involved in the process. In this article, philosophical thinking about a liberating education process is correlated with the Franciscan spirituality which serves as the driving force to realise a more humanising, liberating, and transformative education. The transformative dimension of education can be seen spiritually in the Christian tradition as the experience of repentance, that can happen in the teachers as well as in the students. The philosophical concept of education is used as a basis and rational framework for evaluating the educational process, and then the spiritual inspiration provides a spiritual framework to direct the development of educational process so that it continues to lead to the shared vision that is the goal of Christian educational institutions. This article consists of three parts exploring the philosophical-pedagogical views of Paulo Freire, the spirituality of Francis of Assisi, and the ideas arising from the correlation between the two.